Development of a spectral vegetation index for simultaneous characterization of flowering and foliage development - Casiano Dominguez, Marcos; Paz Pellat, Fernado (REVISTA TERRA LATINOAMERICANA, 2018)
It is important to characterize the phenological patterns of flowering and foliage development in vegetation that has some degree of deciduous behavior due to its relation to the carbon cycle and water. Field techniques and use of digital photograph observation towers have limited geographical scope, so that remote sensing technology is a cost-effective option. In this work a flowering-foliage phenology model was revised and a new model that includes the use of vegetation index of flowering and foliage (VIFF) to characterize and differentiate the patterns is presented. To correlate the VIFF coverage flowering (CF) in vegetation, we conducted a validation experiment that included a low-growing shrub, in which different coverages (<15%) of white flowers were placed. The results showed that the VIFF correlates linearly with the coverage of flowers and the relationship depends on the coverage of the foliage where they are placed. The proposed development allowed establishing clear correlations between VIFF and floral vegetation cover of different coverage area, which was signif icantly effective, even with low percentages of flowering, undetectable with other techniques. Because it uses only red and near infrared bands, the proposed tool is accessible for most applications of remote sensing.